Regulation of cochlear hair cell function by intracellular calcium stores - Ghanshyam P. Sinha; Gregory I. Frolenkov (Frontiers in Cellular Neuroscience)
IntroductionMammalian hearing depends on the dual mechanosensory and motor functions of cochlear hair cells. Both these functions may be regulated by Ca2+ release from intracellular stores. However, it is still unclear how exactly intracellular Ca2+ release may affect either hair cell mechano-electrical transduction (MET) or prestin-dependent electromotility in outer hair cells (OHCs).MethodsHere, we used photo-activatable (caged) compounds to generate fast increases of either Ca2+ or inositol-3-phosphate (IP3) in the cytosol of young postnatal rodent auditory hair cells, thereby stimulating either Ca2+- or IP3- induced releases of Ca2+ from intracellular stores. Fast Ca2+ imaging was used to monitor propagation of Ca2+ signals along the length of a hair cell. To access potential physiological role(s) of intracellular Ca2+ releases, we used whole cell patch clamp to record: i) OHC voltage-dependent capacitance, a known electrical correlate of prestin-based electromotility, and ii) MET currents evoked by stereocilia bundle deflections with fluid-jet. In the latter experiments, changes of mechanical stiffness of the hair bundles were also quantified from video recordings of stereocilia movements.ResultsCa2+ uncaging at the OHC apex initiated Ca2+ wave propagating to the base of the cell with subsequent Ca2+ build-up there. Ca2+ uncaging at the OHC base generated long-lasting and apparently self-sustained Ca2+ responses, further confirming Ca2+-induced Ca2+ release in the OHC basal region. Photoactivated IP3 initiated a slow increase of cytosolic Ca2+ ([Ca2+]i) throughout the whole OHC, confirming the presence of slow-activated IP3-gated Ca2+ stores in OHCs. Interestingly, Ca2+ uncaging produced no effects on OHC voltage-dependent capacitance. In an OHC, the rise of [Ca2+]i is known to decrease axial stiffness of the cell and may modulate the stiffness of mechanosensory stereocilia bundles. To separate these two phenomena, we explored the potential effects of intracellular Ca2+ release on mechanical properties of stereocilia bundles in cochlear inner hair cells (IHCs). Ca2+ uncaging at the apex of an IHC caused a long-lasting increase in mechanical stiffness of stereocilia bundle without any changes in the amplitude or deflection sensitivity of the MET current.DiscussionWe concluded that the most likely physiological role of IP3-gated Ca2+ release at the apex of the cell is the regulation of hair bundle stiffness. In contrast, Ca2+-induced Ca2+ release at the base of OHCs seems to regulate axial stiffness of the cells and its hyperpolarization in response to efferent stimuli, without direct effects on the OHC prestin-based membrane motors.